Potential of Streptomyces avermitilis: A Review on Avermectin Production and Its Biocidal Effect - Ernesto Cerna-Chávez; José Francisco Rodríguez-Rodríguez; Karen Berenice García-Conde; Yisa María Ochoa-Fuentes (Metabolites, 2024)
Secondary metabolites produced by the fermentation of Streptomyces avermitilis bacterium are powerful antiparasitic agents used in animal health, agriculture and human infection treatments. Avermectin is a macrocyclic lactone with four structural components (A1, A2, B1, B2), each of them containing a major and a minor subcomponent, out of which avermectin B1a is the most effective parasitic control compound. Avermectin B1a produces two homologue avermectins (B1 and B2) that have been used in agriculture as pesticides and antiparasitic agents, since 1985. It has a great affinity with the Cl-channels of the glutamate receptor, allowing the constant flow of Cl- ions into the nerve cells, causing a phenomenon of hyperpolarization causing death by flaccid paralysis. The purpose of this work was to gather information on the production of avermectins and their biocidal effects, with special emphasis on their role in the control of pests and phytopathogenic diseases. The literature showed that S. avermitilis is an important producer of macrocyclic lactones with biocidal properties. In addition, avermectin contributes to the control of ectoparasites and endoparasites in human health care, veterinary medicine and agriculture. Importantly, avermectin is a compound that is harmless to the host (no side effects), non-target organisms and the environment.